NAVIGATING LEGAL AMBIGUITY: FOREIGN MILITARY ACTIVITIES AND THE RIGHTS OF ADJACENT STATES UNDER ARTICLE 51(1) UNCLOS 1982 - Lee, Kenneth Lee Maykinho (Veritas et Justitia, 2025)
Article 51(1) of the United Nations Convention on the Law of the Sea (UNCLOS) 1982 exists within the framework of the archipelagic state regime. It provides a legal basis for immediately adjacent neighbouring states to continue exercising existing rights in specific areas that were previously considered international waters but have since come under the jurisdiction of an archipelagic state. The provision refers to these as “other legitimate activities” without offering a clear definition or scope. As a result, the ambiguity of this term undermines legal certainty. A notable example of this issue is the historical disagreement between Indonesia and Singapore over whether military exercises fall within the scope of “other legitimate activities” within Indonesia’s archipelagic waters. This article argues that the term should be jointly defined by the states concerned, as scholars suggest that Article 51(1) constitutes a pactum de contrahendo, thereby necessitating subsequent agreements. By exploring the historical context and scholarly interpretations, this paper seeks to clarify the ambiguous meaning of “other legitimate activities” under Article 51(1) of UNCLOS 1982.